Road Network Rating Based on Land Use of Pokhara - Subedi, Sushmita; Pandit, Roman (Journal on Geoinformatics, Nepal, 2019)
Road Network Analysis considering land use has high potential uses in our country, where the coordination between land use and transportation planning is lacking in many aspects. This research proposes road network analysis based on land use for the current road network of old Pokhara city, one of the urbanizing cities that have led to the rapid urbanization recently. The road network in this city needs to be evaluated to develop efficient and better transportation facility. This study uses Geographic Information System (GIS) to create network database and analyze the current road network based on land use pattern and road attribute, identifying the worst area for transportation supply. This study further evaluates the road network with network volume capacity ratio of the same road section. Rating analysis along with network volume capacity evaluation has provided clear understanding of the links of road network on ward no 8 of Pokhara city having problem with traffic coordination. Among the major roads of the ward 8, Nayabazar road section is found in an unacceptable Level of Service (LOS) but other roads along with the highway passing are within the acceptable limit of LOS.